Computational thinking for the modern problem solver - Riley, David D. 1951- (CRC Press, 2014)
Annotation
Includes bibliographical references. - Online resource; title from title page (Safari, viewed May 6, 2014)
Keywords: Computational intelligence; Logic, Symbolic and mathematical; Rhetoric -- Mathematics; Intelligence informatique; Logique symbolique et mathématique; Rhétorique; Mathématiques; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference